Exploring the Gender Difference and Relationship Study between Marital Satisfaction and Career Success of Individuals Doing Business - Rajashree Kapure (Research Developments in Arts and Social Studies Vol. 4, 2022)
This review evaluates the past decade of research on the determinants of satisfaction and stability in marriage. The study depicts negative communication between spouses would be difficult to change, may not reflect definite change in relationships but might result in distress with change. Dyadic processes suitable for middle-class and more affluent couples compared to lower income couples. Marriage is a vital institution in almost every society on the planet. Multiculturalism has emerged in the twenty-first century as a result of industrialization, urbanization, globalization, and family system fragmentation. In current era of globalization, every individual is particularly concerned about his or her job development, especially at different stages of life. According to the findings, females show a significantly positive correlation between marital satisfaction and level of career success (r = 0.52, p < 0.01) while the score of males on marital satisfaction and career success were negatively related (r = -0.14, p < 0.01). When comparing males and females in terms of career success, there was a significant difference (’t’= 3.23, p < 0.05). While the ‘t’ value for the variable marital satisfaction for both males and females has not been proved (‘t’ =.950). Different factors such as one’s job involvement, professionalism, subjective aspects related to career success, and number of years one completes in his or her profession dominate one’s level of career success, and how women cope with married and professional life may have reflected in their positive correlation with both variables in the female sample.